2000
DOI: 10.1021/es9906406
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Organic Film on an Impervious Urban Surface:  Characterization and Potential Teratogenic Effects

Abstract: Chemical constituents of an organic film collected from an impervious urban surface, namely the exterior surface of windows, have been characterized. The organic portion of this film, that ranged in thickness from 11 to 100 nm, constitutes a previously unrecognized site for exchange of semivolatile organic contaminants in urban environments. The concentrations of total n-alkanes, total polycyclic aromatic compounds (PAH), and total polychlorinated biphenyls (PCB) ranged from 1010 to 22 500, 900 to 62 100, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
180
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(185 citation statements)
references
References 73 publications
3
180
2
Order By: Relevance
“…SAMs formed by reaction of trichloroalkylsilanes on SiO x surfaces, for example on the thin oxide layer on silicon, may be particularly relevant to reactions of organic compounds on dust and on building materials for which silicates can be major components. 208,[238][239][240][241][242][243][244] Another advantage is that silicon crystals are readily available which can be used to make real-time measurements of the oxidation of SAMs attached to their surface using attenuated total reflectance Fourier transform infrared (ATR-FTIR) spectroscopy. In one study, 221 ozonolysis of terminal alkene SAMs with 3-and 8-carbon atoms was observed to give CQO groups as products as expected, at least a portion of which were in the form of carboxylic acids that could be converted to carboxylates by reaction with gaseous NH 3 .…”
Section: This Journal Is C the Owner Societies 2009mentioning
confidence: 99%
“…SAMs formed by reaction of trichloroalkylsilanes on SiO x surfaces, for example on the thin oxide layer on silicon, may be particularly relevant to reactions of organic compounds on dust and on building materials for which silicates can be major components. 208,[238][239][240][241][242][243][244] Another advantage is that silicon crystals are readily available which can be used to make real-time measurements of the oxidation of SAMs attached to their surface using attenuated total reflectance Fourier transform infrared (ATR-FTIR) spectroscopy. In one study, 221 ozonolysis of terminal alkene SAMs with 3-and 8-carbon atoms was observed to give CQO groups as products as expected, at least a portion of which were in the form of carboxylic acids that could be converted to carboxylates by reaction with gaseous NH 3 .…”
Section: This Journal Is C the Owner Societies 2009mentioning
confidence: 99%
“…Some researchers have noted that organic films can be formed through partitioning on these surfaces and have a significant influence on the transportation and fate of SVOCs in urban environments (Law and Diamond, 1998;Diamond et al, 2000;Gingrich et al, 2001). The deposition of SVOCs and wash-off make organic films both a sink and source for various pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…A thin organic film could develop on urban impervious surfaces from the condensation of air contaminants. The few existing studies on this topic show that organic films can range from 11 to 1000 nm in thickness and that the proportion of organic matter ranges from approximately 5e20% (Diamond et al, 2000;Liu et al, 2003b;Wu et al, 2008). Due to the high proportion of organic content of the film, the concentrations of semi-volatile organic compounds (SVOCs) are high on the artificial surfaces of urban areas (Butt et al, 2004;Gingrich et al, 2001;Liu et al, 2003a).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high proportion of organic content of the film, the concentrations of semi-volatile organic compounds (SVOCs) are high on the artificial surfaces of urban areas (Butt et al, 2004;Gingrich et al, 2001;Liu et al, 2003a). SVOCs can accumulate in organic films through the exchange and partitioning of gasphase chemicals with air and/or the direct deposition of particlephase compounds (Diamond et al, 2000;Law and Diamond, 1998;Liu et al, 2003b). Thus, organic films could affect the surface-air exchange and the residence time of SVOCs in urban environments (Priemer and Diamond, 2002).…”
Section: Introductionmentioning
confidence: 99%